Codesign approaches involving older adults in the development of electronic healthcare tools: a systematic review - Karthik Adapa; Lukasz Mazur; Amy C Cole; Amro Khasawneh; Daniel R Richardson (BMJ Open)
Objective The primary aim was to review and synthesise the current evidence of how older adults are involved in codesign approaches to develop electronic healthcare tools (EHTs). The secondary aim was to identify how the codesign approaches used mutual learning techniques to benefit older adult participants.Design Systematic review following the Preferred Reporting Items for Systematic Reviews 2020 checklist.Data sources PubMed, Embase and Scopus databases were searched for studies from January 2010 to March 2021.Eligibility criteria Inclusion criteria were studies employing codesign approaches to develop an EHTs, and the study population was aged 60 years and older.Data extraction and synthesis Data were extracted for analysis and risk of bias. We evaluated the quality of studies using the Agency for Healthcare Research and Quality Evidence-based Practice Center approach.Results Twenty-five studies met the inclusion criteria for this review. All studies used at least two involvement processes, with interviews and prototypes used most frequently. Through cross-classification, we found an increased utilisation of functional prototypes in studies reaching the ‘empower’ level of participation and found that studies which benefitted from mutual learning had a higher utilisation of specific involvement processes such as focus groups and functional prototyping.Conclusions We found gaps to support which involvement processes, participation levels and learning models should be employed when codesigning with older adults. This is important because higher levels of participation may increase the user’s knowledge of technology, enhance learning and empower participants. To ensure studies optimise participation and learning of older adults when developing EHTs, there is a need to place more emphasis on the approaches promoting mutual learning.PROSPERO registration number CRD42021240013.